Genetic Analyses of Wheat and Molecular Marker-Assisted Breeding, Volume 1 Genetics Map and QTL Mapping - Tian, Jichun. (Springer Netherlands : Imprint: Springer, 2015)
The book mainly describes the QTL mappings and efficacy analyses that are associated with wheat productivity, quality, physiology and various stress resistances and provides summaries of results from studies conducted both at home and abroad. It presents comparable data and analyses, helping readers to arrive at a more comprehensive understanding of the latest development in this field. The book provides a wealth of novel information, broad range of applications and in-depth findings on crop genetics and molecular breeding, making it valuable not only for plant breeders but also for academic faculties, senior researchers and advanced graduate students who are involved in plant breeding and genetics. Dr. Jichun Tian is a professor at the Department of Agronomy, Shandong Agricultural University, Tai’an, China.  .